(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Modern methods of teaching foreign languages assumes that for full-fledged verbal communication in a foreign language it is necessary to master the means and types of communicative activities. Among the means of communication, lexical skills occupy a special place. The article discusses the issues of selecting lexical material when teaching a foreign language at a university. It is also emphasized that lexical skills are part of speech skills and their insufficient development can lead to communicative failure.